UJARAN INTEROGATIF BAHASA MELAYU SAMBAS DALAM FILM JEMBATAN JODOH - Hazela, Hesti; Muzammil, Ahmad Rabiâ€™ul; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe background of this research problem is the interrogative utterance of the Sanbas Malay language in the film Jembatan Jodoh as a syntactic study. The problem in this study is how the types, markers, and interrogative sentence patterns in the film Jembatan Jodoh and drama text lesson plans in learning Indonesian in junior high school class 8. Descriptive method. Data collection techniques refer to note taking techniques and note taking techniques. Laptop data collection tools and stationery. Based on the results of the study found five interrogative utterances, namely interrogative sentences asking for acknowledgment of answers, asking for information about one of the elements (functions) of the sentence, asking for reasons, asking for opinions or ideas of others, and presenting. Two markers were found namely -lah and -kah. Four interrogative sentence patterns were found namely Intr + FN, Intr + FAdj, Intr + FNum, Intr + Adver. This research is used as teaching material for learning Indonesian curriculum 2013 in the seventh grade junior high school even semester.Â Keywords: Film Jembatan Jodoh, Interrogatif Speech, Sambas Malay